VD_FINDINFO Jug / 2024 / 357 vom 26. August 2020 - VD Tribunal cantonal (2020)
CONTRAINTE SEXUELLE, TENTATIVEDROIT PÉNAL, EXPULSIONDROIT PÉNAL, VIOL | 49 CO, 19 al. 2 CP, 190 CP, 22 ad 189 al. 1 CP, 66a al. 1 let. h CP, 107 al. 2 LTF